Situação de trabalho e saúde entre cobradores de ônibus urbanos da região metropolitana de Cuiabá-MT - Zandonadi, Francianne Baroni (2007)
The situation of work experienced in life is straightly connected to the health of the workers inserted in anyone inserted in anyone developed function. With the objective to study the relations between the situation of work and the conditions of health of the collectors of a bus enterprise of the metropolitan region of Cuiabá-MT, it was looked to describe the process and the organization of the collectors ´work, demographic partner caractherized the profile and the situation of work, to stabilish the profile of the percieved conditions of health, to appreciate the predominance of the least mental disturbances (DMM) as well as demographic partner annalyzed the association between the incident of DMM and variables made a list to the aspects and to the work situation. For that a study was carried out in two stages:1) Qualitative approach through interviews followed a semi-structured ittinerary with a collectors group and with the immediate leadership; 2) Quantitative approach through a study observacional of cross cut, with 178 collectors in the service of their functions. Through a structure auto-hard-working questionnaire, they were obtained when demographic partner and the situation of work were given. Health problems occurred in the last 15 days (morbity told) and its suspects of DMM (Self reporting questionnaire/SRQ 20). Three main axles were detected regarding the situation of work was compromising of the health; physical conditions of the post of work, organizations storm of the work and interpersonal relations. The perception of several fountains of tension and tiredness from the collectors part demonstrated the painful conditions faced in the situation of work, marked by the robberies, the violence and the fear, which they thought about the profile of above-mentioned problems of healt characterized by disturbances in skull muscles, heart, urogenital, stomachache, headaches, and mental upsets, besides the elevated predominance of suspicion of DMM (34,3%). It was considered an important study that contributed in giving visibilities to the effects of the work to the health of not much studied workers categories, particularly before new questions (like that of the urbane violence) subnotified in the official statistics.